FLAIRectomy in Supramarginal Resection of Glioblastoma Correlates With Clinical Outcome and Survival Analysis: A Prospective, Single Institution, Case Series. Issue 2 (9th October 2020) - Certo, Francesco; Altieri, Roberto; Maione, Massimiliano; Schonauer, Claudio; Sortino, Giuseppe; Fiumanò, Giuseppa; Tirrò, Elena; Massimino, Michele; Broggi, Giuseppe; Vigneri, Paolo; Magro, Gaetano; Visocchi, Massimiliano; et al.
Abstract: Background: Extent of tumor resection (EOTR) in glioblastoma surgery plays an important role in improving survival. Objective: To analyze the efficacy, safety and reliability of fluid-attenuated inversion-recovery (FLAIR) magnetic resonance (MR) images used to guide glioblastoma resection ( FLAIRectomy ) and to volumetrically measure postoperative EOTR, which was correlated with clinical outcome and survival. Methods: A total of 68 glioblastoma patients (29 males, mean age 65.8) were prospectively enrolled. Hyperintense areas on FLAIR images, surrounding gadolinium-enhancing tissue on T1-weighted MR images, were screened for signal changes suggesting tumor infiltration and evaluated for supramaximal resection. The surgical protocol included 5-aminolevulinic acid (5-ALA) fluorescence, neuromonitoring, and intraoperative imaging tools. 5-ALA fluorescence intensity was analyzed and matched with the different sites on navigated MR, both on postcontrast T1-weighted and FLAIR images. Volumetric evaluation of EOTR on T1-weighted and FLAIR sequences was compared. Results: FLAIR MR volumetric evaluation documented larger tumor volume than that assessed on contrast-enhancing T1 MR (72.6 vs 54.9 cc); residual tumor was seen in 43 patients; postcontrast T1 MR volumetric analysis showed complete resection in 64 cases. O6-methylguanine-DNA methyltransferase promoter was methylated in 8/68 (11.7%) cases; wild type Isocytrate Dehydrogenase-1 (IDH-1) was found in 66/68 patients. Progression free survival and overall survival (PFS and OS) were 17.43 and 25.11 mo, respectively. Multiple regression analysis showed a significant correlation between EOTR based on FLAIR, PFS (R 2  = 0.46), and OS (R 2  = 0.68). Conclusion: EOTR based on FLAIR and 5-ALA fluorescence is feasible. Safety of resection relies on the use of neuromonitoring and intraoperative multimodal imaging tools. FLAIR-based EOTR appears to be a stronger survival predictor compared to gadolinium-enhancing, T1-based resection.